Chuyển dịch tiếng Anh như ngôn ngữ thứ hai và mức độ sẵn sàng trong đào tạo sư phạm Tiếng Anh: Bằng chứng từ một cơ sở đào tạo - Nguyen Thi Thu, Huyen; Vương Thị Hải, Yến (Tạp chí Giáo dục, 2026)
Recent policy shifts in Vietnam are recasting English in schooling - not simply as a subject but as a working medium within teaching and learning. This shift brings a different set of expectations for teachers. What is less clear is how far those expectations are reflected in how teachers are being prepared and in how they see themselves in relation to this change. Using a mixed-methods design, this study draws on survey data from 55 pre-service English teachers and 12 teacher educators at one institution, alongside analysis of programme documents. Findings point to a shared awareness of change, but not to a corresponding level of preparedness. Among pre-service teachers, readiness remains largely anticipatory. Among teacher educators, difficulties surface in practice, shaped by existing institutional conditions. Together, these patterns point to a gap in how professional competence is currently framed within the programme - one that is structural rather than attitudinal. Implications are outlined for programme design and teacher educator development. The study contributes empirical evidence of a structural gap between programme goals, stated outcomes and course sequences, one that constrains readiness regardless of how clearly the policy shift is perceived.